The Impact of War on Population Health - Ahmet, Turkan (MacEwan University Student eJournal, 2014)
The past few decades of ongoing war in Iraq has had a dramatic impact on the health of Iraq’s population. Wars are known to have negative effects on the social and physical environments of individuals, as well as limit their access to the available health care services. This paper explores the personal experiences of my family members, who were exposed to war, as well as includes information that has been reviewed form many academic sources. The data aided in providing recommendations and developing strategies, on both local and international levels, to improve the health status of the populations exposed to war.